PENGEMBANGAN MODEL PEMBELAJARAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA BERBASIS DIGITAL DI SEKOLAH DASAR - Yulia, Nurul Mahruzah; Suttrisno, Suttrisno (Dharmas Education Journal (DE_Journal), 2024)
The superiority of the independent curriculum concept makes educational institutions compete to implement this new curriculum with various creativity and new versions of each. Several problems are caused by the lack of ability of educators to manage and integrate regulations, ideas and formulations for the expected competency renewal of students. To realize this good idea, of course a learning model is needed that can be implemented in the classroom, in order to realize the Pancasila student profile. The development of learning models has a positive impact on students' abilities. With the right learning design, students can gain more meaningful experiences and accommodate students' needs. This research is RND research conducted to develop a Learning Model for the Project for Promoting the Profile of Pancasila Students based on Ecosufism in Elementary Schools. This research was conducted using the ADDIE development model with 5 stages. This research produced 6 ideal syntaxes for implementing digital-based learning projects to strengthen Pancasila student profiles: Introduse and preparation, determine the project, agree on the project, create a Timeline as agreed, Monitoring, preparation of results, dissemination of results, and evaluation of results.. This activity was validated by learning experts, Merdeka curriculum experts, and material experts, with good results and can be implemented in elementary school learning.